Measuring breathability and bacterial filtration efficiency of face masks in the pandemic context: A round robin study with proficiency testing among non-accredited laboratories. (15th February 2022) - Tessarolo, Francesco; Nollo, Giandomenico; Benedetti, Luca; Helfer, Fabrizia; Rovati, Luigi; Ferrari, Alberto; Marchetti, Giulio; Reverberi, Federico; Baglio, Salvo; Tuccitto, Nunzio; Stefani, Stefania; Stracquadanio, Stefano; et al.
Highlights: Intra-lot variability impacts uncertainty of face masks performance measurement. BFE measurements above 98% have good repeatability and reproducibility. High uncertainty can be associated to BFE measurements of community masks. Non-accredited laboratories performed at a satisfactory level during pandemic emergency. Face-mask conformity standards should consider uncertainty of BFE and DP measurements. Abstract: Six Italian non-accredited laboratories participated to an interlaboratory study aimed at measuring Differential Pressure (DP) and Bacterial Filtration Efficiency (BFE) of three face-mask models using methods in-line with EN 14683 standard. Methodological non-conformities were annotated. Repeatability and reproducibility on quintuplicate samples were calculated according to ISO 5725-2. Sample stability was also assessed. Laboratories were ranked according to the total standard deviation over all samples and proficiency was evaluated using z-score according to ISO 13528. Although some non-conformities were present, performances for the DP measurements were always acceptable. One laboratory had to revise the bacterial suspension preparation for the BFE test. Overall, non-accredited laboratories working during pandemic emergency performed satisfactorily. Sample-to-sample variability impacted measurement repeatability. BFE values above 98% showed good repeatability (≤1.0%) and reproducibility (≤6.1%), but high BFE uncertainty was associated to community masks. Our findings suggest that relevant face-mask conformity standards should consider uncertainty of BFE and DP measurements.